"A limited focus on cancer rehabilitation"—A qualitative study of the experiences from Norwegian Cancer Coordinators in Primary Health Care. (7th March 2019) - Lie, Nataskja‐Elena Kersting; Solvang, Per Koren; Hauken, May Aasebø
Abstract: Objective: The facilitation of complex cancer rehabilitation interventions in primary health care has become of growing importance to meet the bio‐psycho‐social needs of cancer survivors. However, the delivery of cancer rehabilitation is debated and services are underutilised. Cancer coordinators (CCs) provide patients with coordinated services throughout the trajectory. Little is known about CCs' rehabilitation‐focused tasks. This study's objective was to explore Norwegian CCs' experiences with cancer rehabilitation interventions in primary health care. Methods: Data were obtained via two focus group interviews with 12 participants, analysed using thematic analysis and discussed using Salutogenesis, a theory for health promotion. Results: The analysis revealed three themes: (a) "A missing link" to cancer rehabilitation in primary health care, (b) Aiming to put cancer rehabilitation "in the spotlight, " (c) The need to build a system for rehabilitation service delivery. Conclusion: CCs experience a lacking focus on and missing systems for cancer rehabilitation in primary health care. CCs aim to improve local practices by advocating patients' needs and educating professionals. CCs must be supported via education and training in system‐level work, an increased policy focus and resources for cancer rehabilitation. More research is required into how CCs may facilitate cancer rehabilitation in primary health care.